Supplementation of Ascophyllum nodosum meal and monensin: Effects on diversity and relative abundance of ruminal bacterial taxa and the metabolism of iodine and arsenic in lactating dairy cows - L.H.P. Silva; S.F. Reis; A.T.O. Melo; B.P. Jackson; A.F. Brito (Journal of Dairy Science, 2022)
ABSTRACT: Previous research has shown that the brown seaweed Ascophyllum nodosum (ASCO) has antimicrobial and antioxidant properties and also increases milk I concentration. We aimed to investigate the effects of supplementing ASCO meal or monensin (MON) on ruminal fermentation, diversity and relative abundance of ruminal bacterial taxa, metabolism of I and As, and blood concentrations of thyroid hormones, antioxidant enzymes, and cortisol in lactating dairy cows. Five multiparous ruminally cannulated Jersey cows averaging (mean ± standard deviation) 102 ± 15 d in milk and 450 ± 33 kg of body weight at the beginning of the study were used in a Latin square design with 28-d periods (21 d for diet adaptation and 7 d for data and sample collection). Cows were fed ad libitum a basal diet containing (dry matter basis) 65% forage as haylage and corn silage and 35% concentrate and were randomly assigned to 1 of the following 5 dietary treatments: 0, 57, 113, or 170 g/d of ASCO meal, or 300 mg/d of MON. Supplements were placed directly into the rumen once daily after the morning feeding. Diets had no effect on ruminal pH and NH3-N concentration, which averaged 6.02 and 6.86 mg/dL, respectively. Total volatile fatty acid concentration decreased linearly in cows fed incremental amounts of ASCO meal. Supplementation with ASCO meal did not change the ruminal molar proportions of volatile fatty acids apart from butyrate, which responded quadratically with the lowest values observed at 56 and 113 g/d of ASCO supplementation. Compared with the control diet or diets containing ASCO meal, cows fed MON showed greater molar proportion of propionate. Diets did not affect the α diversity indices Shannon, Simpson, and Fisher for ruminal bacteria. However, feeding incremental levels of ASCO meal linearly decreased the relative abundance of Tenericutes in ruminal fluid. Monensin increased the relative abundance of the CAG:352 bacterial genus in ruminal fluid compared with the control diet. Linear increases in response to ASCO meal supplementation were observed for the concentrations and output of I in serum, milk, urine, and feces. Fecal excretion of As increased linearly in cows fed varying amounts of ASCO meal, but ASCO did not affect the concentration and secretion of As in milk. The plasma activities of the antioxidant enzymes and the serum concentrations of thyroid hormones did not change. In contrast, circulating cortisol decreased linearly in diets containing ASCO meal. The apparent total-tract digestibilities of dry matter, organic matter, and crude protein increased linearly with ASCO meal, but those of neutral and acid detergent fiber were not affected. In summary, feeding incremental amounts of ASCO meal decreased serum cortisol concentration, and increased I concentrations and output in serum, milk, feces, and urine.